Novel Dextran-Supported Biological Probes Decorated with Disaccharide Entities for Investigating the Carbohydrate–Protein Interactions of Gal-3 - Jani Rahkila; Filip S. Ekholm; Ana Ardá; Sandra Delgado; Johannes Savolainen; Jesús Jiménez‐Barbero; Reko Leino (Wiley-VCH Verlag, 2022)
The quest for novel natural‐like biomolecular probes that can be used to gain information on biological recognition events is of topical interest to several scientific areas. In particular, the recognition of carbohydrates by proteins modulates a number of important biological processes. These molecular recognition events are, however, difficult to study by the use of naturally occurring oligosaccharides and polysaccharides owing to their intrinsic structural heterogeneity and to the many technical difficulties encountered during the isolation of sufficient quantities of pure material for detailed structural and biological studies. Therefore, the construction of homogenous biomolecular probes that can mimic both the biophysical properties of polysaccharide backbones and the properties of bioactive oligosaccharide fragments are highly sought after. Herein, synthetic methodology for the construction of well‐defined bioconjugates consisting of biologically relevant disaccharide fragments grafted onto a dextran backbone is presented, and a preliminary NMR spectroscopy study of their interactions with galectin‐3 as a model lectin is conducted.